Unusual Metastatic Patterns of Invasive Lobular Carcinoma of the Breast - Justin D. Sobinsky; Thomas D. Willson; Francis J. Podbielski; Mark M. Connolly (Case Reports in Oncological Medicine)
Invasive lobular carcinoma of the breast has similar patterns of metastatic disease when compared to invasive ductal carcinoma; however, lobular carcinoma metastasizes to unusual sites more frequently. We present a 65-year-old female with a history of invasive lobular breast carcinoma (T3N3M0) treated with modified radical mastectomy and aromatase-inhibitor therapy who underwent a surveillance PET scan, which showed possible sigmoid cancer. Colonoscopy with biopsy revealed a 3 cm sigmoid adenocarcinoma. The patient underwent a lower anterior resection. Pathology showed an ulcerated, invasive moderately differentiated adenocarcinoma extending into but not through the muscularis propria. However, six of seventeen paracolonic lymph nodes were positive for metastatic breast carcinoma (ER+/PR+), consistent with her lobular primary breast carcinoma; there was no evidence of metastatic colon cancer. This case highlights the unusual metastatic patterns of lobular carcinoma.